Molecular beam epitaxy as a growth technique for achieving free-standing zinc-blende GaN and wurtzite AlxGa1-xN - Novikov, Sergei V.; Kent, A.J.; Foxon, C.T. (Elsevier, 2017)
Currently there is a high level of interest in the development of ultraviolet (UV) light sources for solid state lighting, optical sensors, surface decontamination and water purification. III-V semiconductor UV LEDs are now successfully manufactured using the AlGaN material system; however, their efficiency is still low. The majority of UV LEDs require AlxGa1-xN layers with compositions in the mid-range between AlN and GaN. Because there is a significant difference in the lattice parameters of GaN and AlN, AlxGa1-xN substrates would be preferable to those of either GaN or AlN for many ultraviolet device applications. However, the growth of AlxGa1-xN bulk crystals by any standard bulk growth techniques has not been developed so far. There are very strong electric polarization fields inside the wurtzite (hexagonal) group III-nitride structures. The charge separation within quantum wells leads to a significant reduction in the efficiency of optoelectronic device structures. Therefore, the growth of non-polar and semi-polar group III-nitride structures has been the subject of considerable interest recently. A direct way to eliminate polarization effects is to use non-polar (001) zinc-blende (cubic) III-nitride layers. However, attempts to grow zinc-blende GaN bulk crystals by anystandard bulk growth techniques were not successful. Molecular beam epitaxy (MBE) is normally regarded as an epitaxial technique for the growth of very thin layers with monolayer control of their thickness. In this study we have used plasma-assisted molecular beam epitaxy (PA MBE) and have produced for the first time free-standing layers of zinc-blende GaN up to 100 μm in thickness and up to 3-inch in diameter. We have shown that our newly developed PA-MBE process for the growth of zinc-blende GaN layers can also be used to achieve free-standing wurtzite AlxGa1-xN wafers. Zinc-blende and wurtzite AlxGa1-xN polytypes can be grown on different orientations of GaAs substrates - (001) and (111)B respectively. We have subsequently removed the GaAs using a chemical etch in order to produce free-standing GaN and AlxGa1-xN wafers. At a thickness of ∼30 μm, free-standing GaN and AlxGa1-xN wafers can easily be handled without cracking. Therefore, free-standing GaN and AlxGa1-xN wafers with thicknesses in the 30–100 μm range may be used as substrates for further growth of GaN and AlxGa1 xN-based structures and devices. We have compared different RF nitrogen plasma sources for the growth of thick nitride AlxGa1-xN films including a standard HD25 source from Oxford Applied Research and a novel high efficiency source from Riber. We have investigated a wide range of the growth rates from 0.2 to 3 μm/h. The use of highly efficient nitrogen RF plasma sources makes PA-MBE a potentially viable commercial process, since free-standing films can be achieved in a single day. Our results have demonstrated that MBE may be competitive with the other group III-nitrides bulk growth techniques in several important areas including production of free-standing zinc-blende (cubic) (Al)GaN and of free-standing wurtzite (hexagonal) AlGaN.